Perfil socioeconômico e profissional de manipuladores de alimentos e o impacto positivo de um curso de capacitação em Boas Práticas de Fabricação - Devides, Gabriela Gianini Guilherme [UNESP]; Maffei, Daniele Fernanda; Catanozi, Maria da Penha Longo Mortatti [UNESP] (FapUNIFESP (SciELO), 2014)
Foodborne diseases are a worldwide public health problem frequently associated with failures during food handling. Knowledge of the socioeconomic and professional profile of food handlers and their knowledge about the Good Manufacturing Practices (GMP) are required in order to plan public policies and training programs aimed at food safety and quality. This study aimed to evaluate the socioeconomic and professional profile of food handlers and the impact of giving a training course on Good Manufacturing Practices in the city of Araraquara, São Paulo state, Brazil. A total of 192 food handlers answered the following two questionnaires: the first to assess their level of knowledge on GMP, which was applied before (initial evaluation) and after (final evaluation) the training course, and the second to assess the food handlers' socioeconomic and professional profiles. The results showed that the training course had a positive impact on the food handlers' level of knowledge, since all topics on GMP showed a higher percentage of correct answers in the final evaluation than in the initial evaluation. These data indicate the need for continuous training courses to improve the qualification of food handlers, and hence of the food quality and food safety for consumers.

Doenças transmitidas por alimentos constituem um problema de saúde pública em nível mundial e estão frequentemente associadas a falhas na manipulação dos alimentos. Conhecer o perfil socioeconômico e profissional, bem como o nível de conhecimento dos manipuladores de alimentos, é requisito essencial para o planejamento de políticas públicas e programas de capacitação visando a segurança e qualidade dos alimentos. Este trabalho teve por objetivo avaliar o perfil socioeconômico e profissional de manipuladores de alimentos, e o impacto de um curso de capacitação em Boas Práticas de Fabricação (BPF) realizado na cidade de Araraquara-SP, Brasil. Um total de 192 manipuladores respondeu a dois questionários: o primeiro, para avaliar o nível de conhecimento dos manipuladores sobre BPF antes (avaliação diagnóstica) e depois (avaliação final) de participar do curso; o segundo, para realizar um levantamento do perfil socioeconômico e profissional dos manipuladores. Os resultados mostraram que o curso de capacitação repercutiu de forma positiva no nível de conhecimento dos manipuladores, sendo que todos os temas sobre BPF avaliados apresentaram um percentual de respostas corretas significativamente maior na avaliação final em relação à avaliação diagnóstica. Isso indica a necessidade de aperfeiçoamento constante, para garantir a qualificação profissional dos manipuladores e, consequentemente, a qualidade dos alimentos e a segurança alimentar dos consumidores.
Socioeconomic and professional profile of food handlers and the positive impact of a training course on Good Manufacturing Practices
Keywords: Good manufacturing practices; Food handlers; Training course; Socioeconomic and professional profiles; Boas práticas de fabricação; Manipuladores de alimentos; Curso de capacitação; Perfil socioeconômico e profissional